Downregulation of tyrosine threonine kinase inhibits tumor growth via G2/M arrest in human endometrioid endometrial adenocarcinoma. Issue 7 (July 2017) - Zhang, Jiamiao; Jiang, Yan; Zhao, Yu; Wang, Wanxue; Xie, Yiran; Wang, Huating; Yang, Yihua
Endometrial cancer is the most common gynecologic malignancy, about 80% of which is endometrial endometrioid carcinoma. Dysregulation of spindle assembly checkpoint plays a vital role in endometrial endometrioid carcinoma tumorigenesis and progression. The purpose of this study was to explore how tyrosine threonine kinase, a spindle assembly checkpoint–related protein, promotes the endometrial endometrioid carcinoma progression. We found that both messenger RNA and protein levels of tyrosine threonine kinase in endometrial endometrioid carcinoma tissues are higher than those in normal endometrial tissues, and its expression is associated with tumor stages. Genetic depletion of tyrosine threonine kinase by RNA interference in two endometrial endometrioid carcinoma cell lines significantly inhibits cell proliferation and induces apoptosis. Mechanistically, depletion of tyrosine threonine kinase induces G2/M cell cycle arrest and triggers caspase-dependent cell apoptosis. Collectively, tyrosine threonine kinase is significantly upregulated in endometrial endometrioid carcinoma, and downregulation of tyrosine threonine kinase can suppress endometrial endometrioid carcinoma cell proliferation and promote apoptosis via G2/M cell cycle arrest. Our study demonstrates that tyrosine threonine kinase can be a potential therapeutic target for endometrial endometrioid carcinoma treatment.